MOFs‐Assisting Synthesis 3D Ni12P5 Catalyst for Hydrodechlorination of Trichloroethylene. Issue 3 (21st January 2019) - Yuan, Guojun; Bai, Jianliang; Lu, Shaoxiang; Ren, Lili; Gao, Bingying; Mei, Jing; Ma, Yusha; Chen, Xu; Zhang, Lu
Abstract: We reported a new method for producing the 3D Ni12 P5 catalyst. Four regular morphology metal chelates (Ni‐x) were synthesized by nickel nitrate reacting with different metal organic frameworks (MOFs). The 3D materials (Ni−P‐x) were synthesized by hydrothermal reaction with red phosphorus. The phase transition and the morphology change of Ni12 P5 compounds were investigated via X‐ray diffraction (XRD), scanning electron microscopy (SEM), inductively coupled plasma (ICP) and energy dispersive X‐ray spectroscopy (EDS). Moreover, compared with the unmodified catalyst, the catalyst modified with MOFs shows better catalytic activity for hydrodechlorination of trichloroethylene (TCE). The activity of the catalyst improved after calcination at N2 atmosphere. Abstract : This study reported a new method for producing the 3D Ni12 P5 catalyst. The catalyst modified with MOFs shows better catalytic activity for hydrodechlorination of trichloroethylene (TCE).